Perancangan Smart Trash Limbah Rumah Makan Untuk Pemenuhan Pakan Maggot Berbasis IOT - Muhammad Syafaat; Fizar Syafaat (Journal of Embedded Systems, Security and Intelligent Systems, 2023)
The increase in population in urban areas causes food waste production to continue to increase. In 2020, Indonesia has entered an emergency signal for food waste production. Losses from unmanaged food waste reached Rp. 1,011,743,415 annually. The negative impact of food waste which is dominated by organic type waste can cause environmental pollution because it produces dangerous biogas. Most food waste comes from restaurants resulting from leftover food from visitors and leftover ingredients from kitchens that are not managed properly by restaurant owners. In developing alternative feed innovations for several livestock, it was argued that BSF maggot is a good source of natural nutrition for livestock, then the feed from maggot itself comes from organic ingredients in its breeding, but maggot breeders still have difficulty meeting feed from maggot because it only relies on organic feed from household waste around the farm, so the potential for reducing food waste which is dominated by organic waste from restaurants can be utilized by maggot breeders. This study designed a smart trash technology or smart trash bin that can sort organic and non-organic waste based on the internet of things using the Long Range (LoRa) module which will later send data on the availability of organic waste to maggot breeders via a mobile application. The test results from this study show that the entire smart trash system functions properly through blackbox testing, besides that an analysis of data transmission is carried out with the overall Quality of Service results being recommended as good or satisfactory.